Design and construction of a gradient coil for high resolution marmoset imaging. (23rd June 2020) - Handler, William B; Bindseil, Geron; Chaddock, Ryan; Dalrymple, Brian; Gati, Joseph S; Gilbert, Kyle M; Harris, Chad T; Klassen, Martyn L; Peterson, Justin; Van Sas, Frank; Chronik, Blaine A
Abstract: A gradient coil with integrated second and third order shims has been designed and constructed for use inside an actively shielded 310 mm horizontal bore 9.4 T small animal MRI. An extension of the boundary element method, to minimise the power deposited in conducting surfaces, was used to design the gradients, and a boundary element method with a constraint on mutual inductance was used to design the shims. The gradient coil allows for improved imaging performance and was optimized for an imaging region appropriate for marmoset imaging studies. Efficiencies of 1.5 mT m −1 A −1 were achieved in a 15 cm wide bore while maintaining gradient uniformity ≤5% over the 8 cm region of interest. Two new cooling methods were implemented which allowed the gradient coil to operate at 100 A RMS, 25 % of max current with a temperature rise below 30 C.